Tindak Pidana Perdagangan Orang Dalam Perspektif Tindak Pidana Pencucian Uang Di Indonesia - Kurniawan, Wan Rahmat; Hadiyanto, Alwan; Ciptono, Ciptono (JURNAL USM LAW REVIEW, 2024)
The study aims to examine the effectiveness of the implementation of the Act No. 21 of 2007 on the Suppression of Trafficking in Persons (TPPO) from the perspective of the Penal Procedure for Money Laundering (TPPU) in Indonesia. The background to this study is an increasing number of human trafficking cases followed by money laundering, which is a complex and difficult transnational crime. The urgency of this research lies in the need to understand the linkages between the TPPO and the TPPU in order to develop a more effective strategy for dealing with and preventing the two crimes. Research methods use normative jurisprudence. The novelty of this research lies in a comprehensive approach that connects the TPPO with the TPPU through integrated financial analysis and law enforcement. The findings show that the operandi mode of TPPO perpetrators often involves money laundering to cover up illegal funding sources. This research uses normative juridic methods. The findings of the study reveal that the Indonesian law enforcement system still faces significant challenges in addressing the TPPO and TPPU, especially in relation to data integration between law enforcement agencies, immigration, and colonization. The research recommendations include strengthening the legal framework, improved protection for victims, and the development of a more comprehensive policy for crime prevention. This research reaffirms the importance of international cooperation and the use of information technology. Penelitian ini bertujuan untuk mengkaji efektivitas penerapan Undang-Undang Nomor 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang (TPPO) dalam perspektif tindak pidana pencucian uang (TPPU) di Indonesia. Meningkatnya kasus perdagangan orang yang diikuti dengan pencucian uang, yang merupakan kejahatan transnasional kompleks dan sulit diatasi. Urgensi penelitian ini terletak pada kebutuhan untuk memahami keterkaitan antara TPPO dan TPPU guna mengembangkan strategi yang lebih efektif dalam menindak dan mencegah kedua kejahatan tersebut. Metode penelitian menggunakan yuridis normatif. Novelty penelitian ini terletak pada pendekatan komprehensif yang menghubungkan TPPO dengan TPPU melalui analisis keuangan dan penegakan hukum yang terintegrasi. Hasil penelitian menunjukkan bahwa modus operandi pelaku TPPO sering kali melibatkan pencucian uang untuk menyamarkan sumber dana ilegal. Penelitian ini menggunakan metode yuridis normatif. Temuan penelitian mengungkapkan bahwa sistem penegakan hukum di Indonesia masih menghadapi tantangan signifikan dalam mengatasi TPPO dan TPPU, terutama terkait dengan integrasi data antara lembaga penegak hukum, imigrasi, dan kependudukan. Rekomendasi penelitian ini mencakup penguatan kerangka hukum, peningkatan perlindungan bagi korban, dan pengembangan kebijakan yang lebih komprehensif untuk pencegahan kejahatan. Penelitian ini menegaskan pentingnya kerjasama internasional dan penggunaan teknologi informasi.